"If You Buy a Cup, Why Would You Not Use It?" Marital Rape: The Acceptable Face of Gender Based Violence. (2015) - Banda, Fareda
Abstract : There are cases that one never forgets. DPP v. Morgan is one of those for me. I read it as an eighteen-year-old in my first year of law school. It was in the criminal law class where we were being taught about rape. The facts left me shocked and outraged. Morgan went out drinking with his friends. At the end of the night, he invited the friends back to his house. He told them that they could have sex with his wife and added that they should not worry if she appeared to resist, because she liked it that way. The friends duly came over and helped themselves to his wife as per his instructions. Morgan also forced her to have sex with him despite her protestations. She experienced injuries which necessitated medical treatment. His friends were convicted of rape, but he was convicted of indecent assault. This seemed strange. Had they all not forced her to have sex with them despite her clearly expressed refusal? Why was he charged with a lesser crime? The reason was simple: he was her husband. Under the law as it then operated in England, there was no recognition of marital rape. Her consent to lifelong sex on demand, even if it was against her will, was taken as part of the contract of marriage. The words "I do" spoken at the time of the marriage, were taken to mean free access for the husband for as long as they both lived, or until the marriage was legally dissolved or a formal separation was in place.